Clinical arrhythmology and electrophysiology : a companion braunwald's heart disease - Issa, Ziad F. (Elseiver/Saunders, 2012)
With its unique, singular focus on the clinical aspect of cardiac arrhythmias, Clinical Arrhythmology and Electrophysiology: A Companion to Braunwald's Heart Disease makes it easy to apply today's most up-to-date guidelines for diagnosis and treatment. An expert author team provides clear, clinically focused guidance on all types of cardiac arrhythmias, including practical techniques for managing complex patients. Find the information you need quickly with a consistent organization in all chapters, written to a template that shows every arrhythmia type in a similar manner. Access the fully searchable contents online at www.expertconsult.com, in addition to downloadable images and dynamic video clips. Fully understand the rationale for treatment of specific arrhythmias with practical techniques that are grounded in the most recent basic science.